2017
DOI: 10.1016/j.phytochem.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV diphyllin glycosides from Justicia gendarussa

Abstract: In a search for new anti-HIV active leads from over several thousands of plant extracts, we have identified a potent plant lead. The active plant is determined as Justicia gendarussa (Acanthaceae), a medicinal plant that has been used for the treatment of injury, arthritis and rheumatism in Asia including China. Our bioassay-guided fractionation of the methanol extract of the stems and barks of the plant led to the isolation of two anti-HIV compounds, justiprocumins A and B. The compounds are identified as new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Two diphyllin glycosides were obtained from the stems and the barks of J. gendarussa ; justiprocumins A–B ( 110 , 111 ) [80] (Figure 10). Souza et al isolated four alkaloids, brazoides A–D ( 112 – 115 ), squalene, β-sitosterol and lupeol from the ethanol extract of leaves of J. gendarussa [81].…”
Section: Phytochemistry Medicinal Properties and Ethnopharmacologmentioning
confidence: 99%
“…Two diphyllin glycosides were obtained from the stems and the barks of J. gendarussa ; justiprocumins A–B ( 110 , 111 ) [80] (Figure 10). Souza et al isolated four alkaloids, brazoides A–D ( 112 – 115 ), squalene, β-sitosterol and lupeol from the ethanol extract of leaves of J. gendarussa [81].…”
Section: Phytochemistry Medicinal Properties and Ethnopharmacologmentioning
confidence: 99%
“…Although no bio-prospecting and isolation work from the Lao PDR has thus far proceeded to the stage of patent filing thereby meriting additional studies (unlike for Vietnam; Zhang et al, 2014Zhang et al, , 2017, through the VietnamLaos ICBG, six medicinal plant taxa from around the country have been evaluated through the compound isolation stage and have been found to contain mostly novel phytochemicals bearing anti-tuberculosis , anti-malarial (He et al, 2005(He et al, , 2006Libman et al, 2008;Ma et al, 2008); and cancer cell cytotoxicity activities (Zhang et al, 2004). With respect to anticancer bio-prospecting from the ICBG field work conducted from 1998 to 2012 in the Lao PDR, at least 34 species yielded 50 extracts with significant activity (IC 50 < 20 μg/ml) in one or more cancer cell lines of a six cell line panel, which notably led to the isolated compounds asparacoside and 3''-methoxy-nyasol (IC 50 > 4 μg/ml, < 10 μg/ml) from Asparagus cochinchinensis (Lour.)…”
Section: Prior Results and Integrative Programing In Laos Andmentioning
confidence: 99%
“…MOA showed that DGP inhibits ZIKV fusion with cellular membranes and infection by preventing the acidification of endosomal/lysosomal compartments in the target cells [51]. Besides, it also displays potent activity against a broad spectrum of HIV strains with IC 50 values in the range of 15-21 nM [54]; MOA showed that it acts as a potential inhibitor of HIV-1 reverse transcription [55].…”
Section: Substituted Tetrahydrofuransmentioning
confidence: 99%